A Trifluoroethoxyl Functionalized Spiro‐Based Hole‐Transporting Material for Highly Efficient and Stable Perovskite Solar Cells. Issue 2 (15th December 2021) - Zhang, Zheng; Yuan, Ligang; Li, Bin; Luo, Huiming; Wang, Sijing; Li, Zhijun; Xing, Yifan; Wang, Jiarong; Dong, Peng; Guo, Kunpeng; Wang, Zhongqiang; Yan, Keyou
Abstract : It is crucial to finely optimize the properties of hole transport materials (HTMs) to improve the performance and stability of perovskite solar cells (PSCs). Herein, a new spiro‐based HTM (Spiro‐4TFETAD) is developed by replacement of partial methoxy groups in Spiro‐OMeTAD with trifluoroethoxy substituents. Spiro‐4TFETAD has lower highest occupied molecular orbital level, higher thermal stability ( T g = 140 °C), hole mobility (2.04 × 10 −4 cm 2 V −1 s −1 ), and better hydrophobicity with respect to Spiro‐OMeTAD. The PSCs using Spiro‐4TFETAD achieve a power conversion efficiency of 21.11% and excellent humidity resistance. It maintains an average 83% of their initial power conversion efficiency values even in high relative humidity of 60% without encapsulation and 82% of its initial performance after 100 h continuous illumination at the maximum power point. The superior performance underscores the promising potential of the trifluoroethoxyl molecular design in preparing new HTMs toward highly efficient and stable PSCs. Abstract : A trifluoroethoxyl functionalized hole transport material, Spiro‐4TFETAD, is designed and synthesized. Spiro‐4TFETAD shows lower highest occupied molecular orbital level, improved hole mobility, conductivity, and hydrophobicity, as well as effectiveness in minimizing perovskite decomposition, compared to Spiro‐OMeTAD. Spiro‐4TFETAD‐based perovskite solar cells exhibit a power conversion efficiency up to 21.11% with excellent stability, which are superior to those of Spiro‐OMeTAD‐based devices.